Hispanisms, nation and cultural projects Colombia and Mexico: 1886-1921. A study of comparative history - Granados, Aimer (Pontificia Universidad Javeriana, 2014)
This article centers its analysis of the hispanicism as a tendency that in different levels was articulated with Colombia and México national projects during the period among 1886 to 1921. Even though, it shows how in the Colombian case that joint managed to consolidate a traditional conservative cultural project whose referring were taken from the Hispanic tradition. In contrast, in México, after the revolution victory, the relative acceptance that hispanicism have had under the "porfiriato" period was radically denied placing instead a national reborn under the values from one of the principal actors of the revolutionary process, The People. The centrality of popular culture and the interpretations that was made by intellectuals and artists sponsored by the State Consolidated a cultural nationalistic revolutionary project.